Only a woman's word - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
ACP women hoe the fields, hold up the sky and keep the peace. They should be publishing more, too.We are what we eat, goes the old saying. We are also increasingly what we read, and whatever else we absorb from various media: our families,...